ANALISIS PERHITUNGAN BIAYA PRODUKSI TERHADAP PENDAPATAN PADA PENGUSAHA PRODUK LANTING BUMBU KARNING PANCA RASA JATILUHUR - S.E., M.M, Suratno (Jurnal E-Bis (Ekonomi-Bisnis), 2018)
Cost Production is costs incurred to process raw materials into finished products ready tosold. The elements of cost production consist of raw material costs, direct labor, and overhead costs. This study aims to determine and analyze the Calculation of Cost Production to Revenue at Product LantingBumbuKarning/ Panca Rasa in Jatiluhur Village. This study used quantitative methods, the preparation using descriptive analysis is a method that aims to get a picture and description of certain symptoms and explain the relationship between variables based on facts by way of collecting and analyzing data in the form of numbers. Calculation of production cost using full costing method that is by summing all element of raw material cost, direct labor and factory overhead cost. While setting the selling price using the concept of total cost. From the analysis result, it is known that the sales of 2016 quarter I amounted to Rp 31,900,000, the second quarter amounted to Rp 84,100,000 or increased 163.64%, the third quarter decreased by 58.62% or became Rp 34.8 million, and the fourth quarter again increased by Rp 92.800.000 or 166.67%. Meanwhile, the production cost for the first quarter amounted to Rp 24,047,500, the second quarter amounted to Rp 56,167,300 (increased 133.57%), the third quarter was Rp 25,887,600 (decreased 53.91%), and the fourth quarter was Rp 61,606,600 ( 135.87% increase). For operational costs in the first quarter I-IV stable that is Rp 3.600.000. From the unstable total production cost, the net income for the first quarter amounted to Rp 4,252,500, the second quarter amounted to Rp 24,332,700 (472.20% increase), the third quarter was Rp 5,312,400 (decreased 78.17%), and the fourth quarter amounted to Rp 27,593,400 (an increase of 419.41%).